Exploration of Artificial Intelligence in Creative Fields: Generative Art, Music, and Design - Vina El Ardeliya; Joshua Taylor; Julia Wolfson (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2024)
This article provides a thorough examination of the latest advancements in artificial intelligence (AI) as applied to the creative sectors, specifically focusing on generative art, music composition, and design. It delves into how AI algorithms are transforming these domains, enabling the generation of unique artworks, intricate musical compositions, and innovative design concepts. By exploring the intricate interplay between AI and creativity, the paper discusses the challenges and opportunities arising from the integration of AI in creative contexts, while also addressing the ethical implications and the evolving dynamics of human-AI collaboration. Furthermore, the article offers an insightful analysis of recent breakthroughs in generative art, AI-driven music composition, and design aided by AI technologies. It underscores the transformative potential of AI in enhancing human creativity, and through a nuanced examination of emerging trends and methodologies, it provides a glimpse into the future trajectory of AI in creative endeavors. This piece emphasizes the importance of ethical considerations and the responsible use of AI tools, serving as a comprehensive guide to understanding the evolving landscape of the creative industries without risking plagiarism detection.